Comparative Study of Think Talk Write Method and Think Pair Share Method Against Mathematical Communication Ability - Wike Ellissi; Yulita Subianti (AlphaMath : Journal of Mathematics Education, 2020)
The purpose of this research was to know the difference between the use of cooperative learning methods consisting of the think talk write (TTW) method and the think pair share method (TPS) on mathematical communication ability in algebraic forms operating materials. The method used in this research was a quantitative research method using a comparative study approach. The sampling technique used in this study was Cluster Random Sampling. The population of this study consisted of all VII grade students of SMP Negeri 2 Ngabang in the 2019/2020 school year. The research sample was experimental class I namely class VII A using the TTW method and experimental class II namely class VII B using the TPR method. Data was collected using test and documentation. The data analysis technique used was the t-test. The results of this research showed  that the   of 2.049 was greater than the   of 1.995 at the significance level α = 0.05. This means that there were significant differences in the results of students' mathematical communication ability in the aspects of knowledge between the experimental class I compared to the experimental class II. This showed that the experimental class I who followed the learning by applying the Think Talk Write method has a different mathematical communication ability than the experimental class II who followed the learning by applying the Think Pair Share method.